A novel and high-strength Ti–Al–V–Fe alloy prepared by spark plasma sintering. (20th October 2021) - Yang, Xin; Zhang, Zhaoyang; Wang, Ben; Li, Yunzhe; Liu, Gang; Wang, Yan; Zhang, Guangxi; Liu, Shifeng
ABSTRACT: Ti–1Al–8V–5Fe (Ti-185) is a unique low-cost β-Ti alloy, containing lower cost alloying elements, notably Fe, as compared to Ti–10V–2Fe–3Al (Ti-1023) and Ti–5Al–5V–5Mo–3Cr (Ti-5553) while offering high strength. However, with higher Fe content (>5 at.-%), the ' β -flecks' are prone to form because strong segregation in traditional casting, which seriously deteriorates the mechanical properties of the alloys. In this work, Spark plasma sintering (SPS) was successfully used to produce Ti-185 components starting from elemental Ti and Al powders, and a V–Fe master alloy powder with different particle size (106, 45, and 23 μm). SPS can be used to produce a very fine grain microstructure with decreasing particle size master alloy powder and non-detrimental Fe segregation, and which result in a significant improvement of the mechanical properties. As the particle size of the FeV80 powder decreases, the compressive strength, yield strength and compressive strain of the alloy gradually increase.